Realidade e discurso na pós-graduação stricto sensu: O que consolidar? O que expandir? - de Luna, Sergio Vasconcelos (Revista Cocar, 2012)
O texto discute a Pós-Graduação Stricto Sensu"no Brasil e apresenta reflexões sobre os limites"e possibilidades das linhas de pesquisa e sua"produção intelectual, bem como a formalização"e o modelo implantado no país, objetivos e as"razões pelas quais a Pós-Graduação vem sendo"procurada, o repertório trazido pelos candidatos,"o processo de seleção e as oportunidades"oferecidas por tais cursos. Por fim, apresenta"sugestões para melhoria do Sistema. " Palavras-Chave: Educação. Stricto Sensu. Avaliação. Política Educacional. " Reality and discourse in the stricto sensu post-graduation: what to consolidate? What to expand? The text discusses the"Stricto Sensu"Post- Graduation in Brazil and presents some reflections on the limits and possibilities related to the research lines and their intellectual production, as well as the formalization and the model established in this country, objectives and reasons why the Post-graduation has been sought, the repertoire students bring with them, the process of selection and the opportunities offered by these courses. At last, it presents some suggestions to improve the System. " " <!–[if !supportTextWrap]–>Keywords:"Education. Stricto Sensu. Evaluation. Educational Policy. <!–[endif]–> " "